2023
DOI: 10.3389/fimmu.2023.1150572
|View full text |Cite
|
Sign up to set email alerts
|

“Cross-talk” between gut microbiome dysbiosis and osteoarthritis progression: a systematic review

Abstract: ObjectivesThe aim of this systematic review was to summarize the available literature on gut microbiome (GMB) and osteoarthritis (OA), analyze the correlation between GMB and OA, and explore potential underlying mechanisms.MethodsA systematic search of the PubMed, Embase, Cochrane, and Web of Science with the keywords “Gut Microbiome” and “Osteoarthritis” was conducted to identify the human and animal studies exploring the association between GMB and OA. The retrieval time range was from the database inception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Translocation of bacteria from the gastrointestinal tract through a permeable gut barrier has been postulated as a driver of surgical site infections [ 40 ]. Gut microbiota, intestinal permeability, GI inflammation, and other gut-associated factors are proposed to contribute to OA, so this phenomenon could also occur in the absence of clinical infection and could include bacterial byproducts [ 16 , 41 , 42 ]. Boer et al found that gut dysbiosis is associated with joint pain and inflammation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Translocation of bacteria from the gastrointestinal tract through a permeable gut barrier has been postulated as a driver of surgical site infections [ 40 ]. Gut microbiota, intestinal permeability, GI inflammation, and other gut-associated factors are proposed to contribute to OA, so this phenomenon could also occur in the absence of clinical infection and could include bacterial byproducts [ 16 , 41 , 42 ]. Boer et al found that gut dysbiosis is associated with joint pain and inflammation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that gut dysbiosis worsens osteoarthritis ( 91 ). A causal relationship has been established among microbial taxa such as Methanobacteriaceae, Ruminiclostridium, Desulfovibionale s and osteoarthritis ( 92 ).…”
Section: Bioactives and Osteoarthritis: Metabolic And Anti-inflammato...mentioning
confidence: 99%
“…A strong relationship between OA and GM has been emerging in recent years since GM dysbiosis (an alteration in the amount, composition and diversity of microbiota [ 17 ]) can disrupt the gut barrier, activate the “gut–joint axis”, modulate innate and adaptive immunity through LPS release, short-chain fatty acid modification, macrophage activation, cytokine liberation, regulation of T-cell responses and B cells differentiation [ 18 , 19 ]. Moreover, GM can influence OA progression by interacting with other OA risk factors such as age, sex, obesity, inflammation, and mechanical load [ 20 ].…”
Section: Introductionmentioning
confidence: 99%